Effect of Magnetopriming on Photosynthetic Performance of Plants - Sarraf, Mohammad; Deamici, Kricelle Mosquera; Taimourya, Houda; Islam, Monirul; Kataria, Sunita; Raipuria, Ritesh Kumar; Abdi, Gholamreza; Brestic, Marian (International journal of molecular sciences, 2021)
Magnetopriming has emerged as a promising seed-priming method, improving seed vigor, plant performance and productivity under both normal and stressed conditions. Various recent reports have demonstrated that improved photosynthesis can lead to higher biomass accumulation and overall crop yield. The major focus of the present review is magnetopriming-based, improved growth parameters, which ultimately favor increased photosynthetic performance. The plants originating from magnetoprimed seeds showed increased plant height, leaf area, fresh weight, thick midrib and minor veins. Similarly, chlorophyll and carotenoid contents, efficiency of PSII, quantum yield of electron transport, stomatal conductance, and activities of carbonic anhydrase (CA), Rubisco and PEP-carboxylase enzymes are enhanced with magnetopriming of the seeds. In addition, a higher fluorescence yield at the J-I-P phase in polyphasic chlorophyll a fluorescence (OJIP) transient curves was observed in plants originating from magnetoprimed seeds. Here, we have presented an overview of available studies supporting the magnetopriming-based improvement of various parameters determining the photosynthetic performance of crop plants, which consequently increases crop yield. Additionally, we suggest the need for more in-depth molecular analysis in the future to shed light upon hidden regulatory mechanisms involved in magnetopriming-based, improved photosynthetic performance.
Keywords: Magnetic Fields; fluorescence; rostlinné proteiny; chlorofyl; rostliny; Plant Proteins; Plants; Fluorescence; Photosynthesis; Chlorophyll; Plant Leaves; Seeds; listy rostlin; fotosyntéza; magnetické pole; semena rostlinná